How are Mentees’ Goals and Demographic Characteristics Associated with their Mentoring Experiences, Preferences and Perceived Benefits? - Wekam, Vanina (East Carolina University, 2021)
Mentoring plays a key role in STEMM (Science, Technology, Engineering, Mathematics and Medicine) because it increases the likelihood that students persist in a program and successfully move into their chosen career. Mentoring typically happens in a dyadic form where a senior mentor advises a mentee who is not as experienced. Recent review of the literature suggests that other forms of mentoring could be beneficial to mentees. Group mentoring is where a mentor or multiple mentors work with a mentee or several mentees. Group mentoring can take on many forms such as mentoring triads, collective mentoring with more than three individuals in the mentoring relationship, and a mentoring network with different information, resources, and people to help guide a mentee. Mentoring can also be either formal (where a designated mentor or multiple mentors are assigned to a mentee or multiple mentees) or informal (where the mentoring relationship evolves spontaneously between mentor(s) and mentee (s)). Two major goals that have been documented for a mentoring relationship are career and psychosocial goals. Career goals prepare the mentee for career advancement opportunities and include functions such as sponsoring, coaching, protecting, increasing the mentees exposure or visibility, and providing challenging work assignments. Psychosocial goals provide a sense of confidence and competence for the mentee and include functions such as role modeling, accepting, confirming, counseling, and offering friendship. It is possible that the type of mentoring, as well as demographic factors, can influence one's access to mentors and the likelihood of fulfilling one's goals for the mentoring relationship. For example, research has shown that both formal and informal mentoring relationships may provide support for the mentee's advancement, but underrepresented (UR) groups in science or medical fields (e.g., black students or those from low-income households) may have more difficulty accessing the benefits associated with informal mentoring. This study seeks to investigate how medical students' mentoring goals and demographic characteristics (race/ethnicity, gender identity, household income, or parental highest level of education) may have influenced their prior mentoring experiences. I focus on medical students because their insight on their mentoring experiences would be beneficial for students interested in pursuing a career in medicine. I surveyed 87 medical students from three different institutions (East Carolina University's Brody School of Medicine (SOM), Wake Forest SOM and UNC Chapel Hill SOM) and holding one-on-one interviews with ten of the survey respondents. The goals of the study were to provide a deeper understanding of the factors that may impact mentoring and to advance ongoing research about effective mentoring in higher education. Findings show that medical students from all populations had previously participated in both formal and informal mentoring, and Asian students had significantly more informal mentors than white and UR students. Medical students generally had university faculty or medical professionals as mentors, and there was a significant association between the gender identity of the mentee and that of their first mentor (i.e., they shared the same gender identity). Additionally, students reported having both career and psychosocial goals for mentoring, and there was a positive association between the strength of the mentees' goals for mentoring and the number of formal mentors the mentees had. Most respondents preferred having one mentor in a dyadic relationship, but only around a quarter of the survey respondents had experienced group mentoring. Further research into the functions and benefits of group mentoring will be critical to better anticipate under what conditions it may be preferable over dyadic mentoring. Mentoring programs for aspiring medical students may benefit from focusing on both career and psychosocial functions, as well as offering access to dyadic and group mentoring, to maximize the benefits of mentoring for students from diverse backgrounds.
Keywords: Mentoring; Higher Education; STEMM; Mentoring in science; Strategic planning; Medical colleges; Interpersonal relations